"Bring Your Whole Self to the Work": Identity and Intersectional Politics in the Louisville LGBTQ Movement. (1st April 2016) - Fosl, Catherine; Kelland, Lara
Abstract: This essay examines the interpretive use of intersectionality in oral history scholarship. The authors raise questions about how recent social movement participants grapple with multiple and overlapping social identities, as reflected in a body of interviews with LGBTQ activists connected to an organization called the Fairness Campaign in Louisville, Kentucky. The Fairness Campaign originated in 1991 as a mostly white-led but coalition-oriented LGBTQ rights organization, distinguishing itself for its racial and wider social justice focus. The authors ultimately suggest that intersectionality is a valuable theoretical framework for oral historians working on the LGBTQ and other identity-based social movements of the past half century